DETERMINANTS OF PROCUREMENT OPTIMISATION IN SELECTED COUNTY GOVERNMENTS IN KENYA. - Kinuthia, Clare Wanjiku; Kihara, DR. Allan (International Journal of Supply Chain and Logistics, 2019)
Purpose: The study was to determine the factors affecting procurement optimization in selected county governments in Kenya with an aim of making recommendations. The study sought to establish the effect of vendor management, risk management, information technology adoption and value for money effect on procurement optimization. To achieve this, the researcher reviewed both theoretical and empirical literature and proposed the research methodology that addressed the gaps identified in literature as well as answer the stipulated research questions. The study employed a descriptive research design. Methodology: The study targeted 136 respondents including the Chief Finance Officers in charge of Finance and Economic Planning, Heads of the Supply Chain Management Unit and Procurement staff at the departmental level. The researcher prefers this method because it allows an in-depth study of the subject. Data was collected using self-administered questionnaires. The target population was the procurement staff at each county government. Pilot study was carried out to establish the validity and reliability of the research instruments. The instruments were designed appropriately according to the study objectives. The data collected were analyzed by use of descriptive and inferential statistics. The study used multiple regression and correlation analysis to show the relationship between the dependent variable and the independent variables. The data generated were keyed in and analyzed by use of Statistical Package of Social Sciences (SPSS) to generate information which was presented using charts, frequencies and percentages. Results: The study found that vendor managed inventory systems, material resource planning and bar coding of items were deduced to play a significant influence in cost reduction, in lead time reduction and in increasing customer satisfaction. The study concluded that information technology adoption greatest effect on procurement optimization in selected county governments in Kenya followed by vendor management then value for money while risk management had the least effect on the procurement optimization in selected county governments in Kenya in Kenya. Contribution to policy and practice: The study recommended for the county governments to ensure that there is use inventory management system and automated recording, cycle counting Inventory control; use of E.O.G and that it's important for the county governments to Identify and deal with risks proactively.